Impact of Leadership Competence, Leadership Strategies, Efficient and Effective Administrative Functions on Performance - Alito Pereira Maia (CV. Ulil Albab Corp, 2024)
Impact of leadership competence, leadership strategies, efficient and effective administrative functions on performance. The variable of leadership competencies has a positiveimpact on performance, based on research and performance models with a value of t = 6.273 or> a large P value of 2.004 and a positive coefficient of 0.02 <0.05. This research proves that the impact of leadership competencies is done by leadership and its impact on the organization, giving advantages over other organizations. Leadership has a role and success in achieving organizational goals. Leadership strategy is positively related to influence and significant performance, as shown by a significant value of t = 4.140> 2.004 and a significant value of 0.00 <0.05. The efficient administrative function variable has a positive influence on performance because the statistical value = 4.512 <the< span=